2015
DOI: 10.5114/wiitm.2015.52082
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer liver metastases: laparoscopic and open radiofrequency-assisted surgery.

Abstract: IntroductionThe liver is the most common site of colorectal metastases (colorectal liver metastases – CLM). Surgical treatment in combination with oncological therapy is the only potentially curative method. Unfortunately, only 10–25% of patients are suitable for surgery. Traditionally, open liver resection (OLR) is usually performed. However, laparoscopic liver resection (LLR) has become popular worldwide in the last two decades.AimTo evaluate the effectiveness and benefits of radiofrequency minor LLR of CLM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…A previous study reported that definite ablation can be achieved for tumors with a diameter of < 3 cm. However, tumors measuring > 3 cm are associated with the possibility of incomplete ablation, which is consistent with the results of this research [ 16 19 ]. The minimally invasive and reproducible nature of laparoscopic microwave ablation entails no significant differences in terms of ablation effect and follow-up results between patients receiving a second ablation and those with tumors measuring < 3 cm in diameter.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study reported that definite ablation can be achieved for tumors with a diameter of < 3 cm. However, tumors measuring > 3 cm are associated with the possibility of incomplete ablation, which is consistent with the results of this research [ 16 19 ]. The minimally invasive and reproducible nature of laparoscopic microwave ablation entails no significant differences in terms of ablation effect and follow-up results between patients receiving a second ablation and those with tumors measuring < 3 cm in diameter.…”
Section: Discussionsupporting
confidence: 91%
“…Initial screening of abstracts led to the exclusion of 383 articles. Besides, six were further excluded by a close scrutiny of remaining articles: 1 35 only included OLR, 3 duplicates 24,36,37 , 1 38 did not report outcomes of interest and 1 39 used radiofrequency ablation. Finally, 32 non-randomized comparative studies were included in our meta-analysis 20,26,27,4068 .
Figure 1Study selection flow chart according to PRISMA statement.
…”
Section: Resultsmentioning
confidence: 99%
“…In recent years more and more studies support laparoscopy as an alternative to “open surgery” for liver resection for benign lesions as well as malignant tumours [ 17 ]. A laparoscopic approach for cystic echinococcosis has also been the subject of a number of studies [ 10 , 18 ].…”
Section: Discussionmentioning
confidence: 99%